Management and treatment of chronic hepatitis B in HIV-positive patients. (August 2014) - Soriano, Vincent; de Mendoza, Carmen; Fernández-Montero, José V.; Labarga, Pablo; Barreiro, Pablo
Abstract Chronic hepatitis B virus (HBV) infection is common in HIV-positive individuals, mainly among those with sexually risky behaviors. Although HBV vaccination is mandatory in all HIV-infected persons with negative HBV markers, lower rates of protection due to abnormal immune responses are achieved. HIV accelerates the course of liver disease caused by chronic HBV infection, leading rapidly to end-stage hepatic illness and increasing the risk of hepatocellular carcinoma. Treatment of HIV including nucleos(t)ide analogues active against HBV highly improves outcomes, especially when tenofovir is part of the antiviral regimen. The use of lamivudine as the only active anti-HBV agent in HIV-HBV co-infected patients should be limited to individuals with low serum HBV-DNA levels. Otherwise, selection of drug resistance may eliminate any clinical benefit, produce cross-resistance to other antivirals, and favor the emergence of HBV vaccine escape mutants.